Implementasi Perpajakan Affiliate Marketer Shopee dalam Sudut Pandang Hukum Pajak dan Hukum Islam - Sitah, Putri Dwi; Rumawi, Rumawi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The development of information technology brings significant changes in the business world, one of which is through the Shopee affiliate marketer program that provides opportunities for individuals to earn income through commissions from product sales. However, the tax practice of affiliate marketer income still requires in-depth study, especially in the perspective of tax law and Islamic law. The main problem in this research is how the Income Tax (PPh) payment mechanism for Shopee affiliate marketers and its compliance with the provisions of taxation law and the principles of Islamic law. This research aims to find out and analyze 1) To find out the percentage of PPh for shopee affiliate marketers in the perspective of tax law and Islamic law. 2) To know how to pay PPh for affiliate marker shopee in the perspective of tax law and Islamic law. The research method used is a legal sociology approach with a type of empirical legal research. Data is collected through observation, interview, and documentation of Shopee affiliates and sellers, and analyzed using data reduction techniques, data presentation, and drawing conclusions. The research results show that: 1) the percentage of PPh of shopee affiliate marketers is the commission received by Shopee affiliates, which is the object of PPh Article 21 and is subject to a progressive tax rate according to Government Regulation No. 58 Year 2023, based on the taxation of 50% of the total gross commission. The tax rate starts from 5% for income up to Rp60 million and increases according to the income layer. 2) The payment method of PPh affiliate marketer shopee is that Shopee deducts and deposits taxes automatically before the affiliate receives the commission, and requires the inclusion of NPWP so that the tax rate is lower. In the perspective of Islamic law, the obligation to pay taxes (dharibah) is recognized as long as it is managed fairly and used for public benefit, and does not burden the community. In conclusion, the practice of paying PPh affiliate marketer Shopee is in accordance with the provisions of the applicable tax law and can be accepted from the perspective of Islamic law as a form of contribution to the welfare of the community.